Imaging of living cells and zebrafish in vivo using a ratiometric fluorescent probe for hydrogen sulfide. Issue 21 (24th September 2015) - Liu, Tianbao; Lin, Jie; Li, Zhen; Lin, Lin; Shen, Yuning; Zhu, Hailiang; Qian, Yong
Abstract : We have developed a novel colorimetric and ratiometric fluorescence probe for the selective and sensitive imaging of H2 S in living cells and living zebrafish in vivo . Abstract : We have developed a novel colorimetric and ratiometric fluorescence probe for the selective and sensitive monitoring of hydrogen sulfide based on a dicyanoisophorone platform. An excellent linear relationship of fluorescence intensity ratio ( I 637 / I 558 ) ( R 2 = 0.9867) versus hydrogen sulfide concentration in the range of 1–12 μM was obtained. This probe exhibited a remarkable fluorescence response to hydrogen sulfide over other physiological thiols or biological species, which fluoresces in the red region with a large Stokes shift (172 nm). This probe was successfully utilized to monitor H2 S under in vitro physiological conditions and for imaging H2 S in living cells and living zebrafish in vivo .